Heterosis in oblong fruited tomato (Solanum lycopersicum) hybrids for growth and yield traits - KHAPTE, P S; JANSIRANI, P; SARASWATHI, T (The Indian Journal of Agricultural Sciences, 2019)
In the present investigation, oblong fruited nine tomato lines were crossed in full diallel mating design to produce 72 F1 hybrids. Heterobeltiosis and standard heterosis were estimated for growth, fruit yield and quality traits in F1 hybrids. The parental lines, viz. BRML (P3), Arka Ashish (P4), Vybhav (P5), IIVR-L (P6), EC 608406 (P7) and EC 608395 (P8) were found most promising for exploiting heterosis. Considering all the cross combinations individually, the hybrid combinations that out fielded their parents for a maximum number of components for heterobeltiosis and standard heterosis coupled with highper se values were; IIVR-L×Arka Ashish (P6× P4), IIVR-L×Vybhav (P6× P5), EC 608406 × BRML (P7× P3), EC 608395 ×IIVR-L (P8× P6) and EC 608406 ×IIVR-L (P7× P6). However, hybrids those performed better for yield parameters were not heterotic significantly for quality parameters except P7× P3. The standard heterosis noted in outperforming hybrids P7× P3 (23.99% and 19.80%) and P6× P4 (18.97% and 14.95%) over check hybrids NUN 5024 and COTH-3 respectively. The yield per plant based on per se values were also highest in hybrids P7× P3 (3.91 kg) and P6× P4 (3.75 kg). These promising hybrids could beused for dual purpose (fresh market as well as processing), since they have improved economic traits besides good fruit quality parameters (high TSS) and oblong in shape.